Surveys of butterfly and skipper fauna in the southwestern part of the Republic of Macedonia (Lepidoptera: Papilionoidea & Hesperioidea) - Vid Švara; Miloš Popović; Andrej Peternel; Đorđe Radevski; Kaja Vukotić; Rudi Verovnik (Natura Sloveniae)
Data from four surveys within the last six years were combined in order to improve the knowledge of the butterfly distribution in the Republic of Macedonia. These surveys covered a total of 40 localities, with special emphasis on less sampled areas of the south-western part of the country. The study yielded recording of 131 species, including several habitat specialist and potentially threatened butterflies. Interesting records for the following species are discussed in detail: Muschampia tessellum, Anthocharis gruneri, Euchloe penia, Tarucus balkanicus, Cupido alcetas, Pseudophilotes bavius, Polyommatus aroaniensis, Polyommatus escheri, Araschnia levana and Melitaea ornata. Ten species observed are considered threatened at the European level and 18 of them at the country level. This proves high conservation value of the studied region with many butterfly rich habitats still preserved. The lack of concerted effort for mapping of butterfly fauna in Macedonia is discussed and priorities for future surveys given.